Iron-Fortified Drinking Water Studies for the Prevention of Children's Anemia in Developing Countries - Jose E. Dutra-de-Oliveira; J. Sergio Marchini; Joel Lamounier; Carlos A. N. Almeida (Anemia)
Anemia and iron deficiency should receive special attention considering their high prevalence and serious consequences. For prevention, globally it is recommended to increase dietary iron intake, iron fortification of industrialized foods, and medical iron supplementation. Food fortification for the prevention of iron deficiency in developing countries should consider carriers locally available and consumed daily, requiring limited infrastructure and technology. Drinking water is the iron carrier we have been working for years for the prevention of iron deficiency and anemia in small children in Brazil. It was shown that studies with iron-fortified drinking water were proved to be effective on children's anemia prevention. Water is found everywhere, consumed daily by everyone may be easily fortified with simple technology, is low priced and was effective on the prevention of children's anemia. Fortification of drinking water with iron was locally implemented with the direct participation of the government and community. Government authorities, health personnel and population were part of the project and responsible for its community implementation. The mayor/municipality permitted and supported the proposal to supply it to children at their day-care centers. To keep the children drinking water iron fortified supply an officially authorized legislation was also approved.